The clinical and immunological features of the post-extracorporeal shock wave lithotripsy anti-glomerular basement membrane disease - Wang, Beining (Ren Fail, 2021)
INTRODUCTION: Extracorporeal shock wave lithotripsy (ESWL) is a noninvasive modality to treat urolithiasis, with complications including tissue damage and hematoma of kidney parenchyma. Anti-glomerular basement membrane (GBM) disease is suggested to be a rare complication of ESWL since it was reported in several cases to occur after ESWL. However, the clinical and immunological features of the ESWL-associated anti-GBM disease have not been fully investigated so far. CASE PRESENTATION: Here, we present the clinical, pathological, and immunological characteristics of three patients with the post-ESWL anti-GBM disease in our hospital. Anti-GBM disease occurred within a median of 22 months after ESWL treatment. It presented with similar clinical features to the classic anti-GBM disease, including fever, gross hematuria, and rapidly progressive glomerulonephritis (RPGN) with poor renal prognosis. Sera from all patients recognized the α3(IV)NC1 in GBM, but with IgG2 and IgG4 as the dominant IgG subclasses. CONCLUSION: Although further exploration is required to prove the causal relationship in this rare condition, our study reminds physicians that patients developing acute renal insufficiency after ESWL should lead to the suspicion of anti-GBM disease and in-time diagnosis and treatment.